The Many Colors Children See: Development and Intervention of Children’s Social Prejudices - Yopina G Pertiwi (Faculty of Psychology Universitas Gadjah Mada, 2017)
In light of the current socio-political situation that magnifies the majority-minority group division in the country, it is essential for parents and other elements of the society to discuss about how this situation may affect the development of the next generation. Both explicit and implicit information on social categorization provided by adults and other resources assist in the formation of children’s stereotype and prejudice towards various social groups. This paper reviews empirical studies on the development of prejudice across childhood and the strategy that can potentially facilitates the reduction of prejudice among children. It is evident that children have begun to use social categories to describe different social groups from a very young age and promoting intergroup contact may be used as a promising solution to lower prejudice among children.